Diplomasi Indonesia dan Persoalan Migran Asal Indonesia Pasca Konflik Suriah - Mutmainah, Dian (Department of International Relations, Universitas Brawijaya, 2024)
The repatriation of Indonesian migrants from Syria in April 2023 reminded us to the repatriation wave of Indonesian migrant from Syria after the country was torn by internal conflict since 2011. Indonesian Government has conducted series of diplomatic efforts to ensure the safety of its citizen in Syria. Indonesian Government was decided to stop sending its workers to Syria since 2011. Indonesia also categorized Syria as one of rescticted destinations for its migrant workers since 2015. Then why are there Indonesian migrants in Syria after those restrictions was applied? This fact indicates that there was illegal procedure available that enabled the workers to migrate to Syria amids the restrictions which out of sight of the government monitor. This paper addressed two issues: Indonesian diplomacy as a respon to the conflict in Suriah; and the problems faced by Indonesian Migrant Workers (IMW) because of the conflict in Syria. This paper identified two problems faced by IWM in Syria after the conflict: security threats caused by the conflict that contributes to the occurrence of illegal migration to Syria; and labour issues that wosened by intensity of illegal migration during the conflict.